Absolute upconversion quantum yields of blue-emitting LiYF4:Yb3+, Tm3+ upconverting nanoparticles. Issue 35 (29th August 2018) - Meijer, Michael S.; Rojas-Gutierrez, Paola A.; Busko, Dmitry; Howard, Ian A.; Frenzel, Florian; Würth, Christian; Resch-Genger, Ute; Richards, Bryce S.; Turshatov, Andrey; Capobianco, John A.; Bonnet, Sylvestre
Abstract : Absolute quantum yields for the individual emission bands in blue-emitting LiYF4 :Yb 3+, Tm 3+ UCNPs are reported, measured over a broad excitation power range by three independent research centers. Abstract : The upconversion quantum yield ( Φ UC ) is an essential parameter for the characterization of the optical performance of lanthanoid-doped upconverting nanoparticles (UCNPs). Despite its nonlinear dependence on excitation power density ( P exc ), it is typically reported only as a single number. Here, we present the first measurement of absolute upconversion quantum yields of the individual emission bands of blue light-emitting LiYF4 :Yb 3+, Tm 3+ UCNPs in toluene. Reporting the quantum yields for the individual emission bands is required for assessing the usability of UCNPs in various applications that require upconverted light of different wavelengths, such as bioimaging, photocatalysis and phototherapy. Here, the reliability of the Φ UC measurements is demonstrated by studying the same batch of UCNPs in three different research groups. The results show that whereas the total upconversion quantum yield of these UCNPs is quite high—typically 0.02 at a power density of 5 W cm −2 —most of the upconverted photon flux is emitted in the 794 nm upconversion band, while the blue emission band at 480 nm is very weak, with a much lower quantum yield of ∼6 × 10 −5 at 5 W cm −2 . Overall, although the total upconversion quantum yield of LiYF4 :Yb 3+, Tm 3+ UCNPs seems satisfying, notably for NIR bioimaging, blue-light demanding phototherapy applications will require better-performing UCNPs with higher blue light upconversion quantum yields.